Prevalence and health-seeking behavior of leprosy patients at Universitas Mataram Hospital - Krisnanti Putri, Wayan Julita; Hapsari, Yunita; Kusuma, Dinie Ramdhani (Universitas Gadjah Mada, 2024)
Purpose: This study aims to acknowledge leprosy patients' prevalence and health-seeking behavior at the outpatient clinic of UNRAM Hospital. Methods: This study used a retrospective cohort design of leprosy patients from January 2021 to April 2023. Results: There were 40 leprosy patients, including 35 patients (87.5%) with multibacillary type, and five patients (12.5%) were identified as paucibacillary type. This study included 21 men (52.5%) and 19 women (47.5%). Based on age, the most frequent group came from people aged around 26-45 years old (45%). There were 16 unemployed patients (40%) and 14 (35%) senior high school graduates. Mataram had the most leprosy cases (52.2%) in UNRAM hospital. There were 20 cases (50%) of Type 1 reaction and 32 patients (80%) who received multidrug therapy. There were 21 patients (52.5%) who developed a disability. Most patients (45%) came to the clinic several times yearly. They were mostly female (56%), while men went to the clinic at least once yearly (67%). Patients under 45 (67%) and those with lower educational levels (78%) came more frequently than other groups. Conclusion: The prevalence of the study is important for realizing the burden of the disease and establishing a preventive approach towards leprosy. The role of health providers is important in engaging the awareness of leprosy patients’ self-care because it is important to prevent serious disabilities.